Early Modern Justice and Oral Traditions: Crime and Punishment in Breton Ballads. Issue 1 (2nd January 2019) - Guillorel, Éva
Abstract : Breton ballads singing tales of crime and justice have been collected by ethnographers since the nineteenth century. These songs refer to a number of episodes of crime and violence that took place during the ancien régime. Composed shortly after the events they describe, they were passed on by families and communities over centuries, almost exclusively in oral culture, since printed broadsheets of these songs were not produced in the early modern period. The Breton ballads give privileged access to the omnipresent sonic element of early modern culture, since singing leaves few traces in the written and visual sources typically studied by researchers. Comparing the ballads with documents from the criminal archives concerning the same or similar cases reveals how communities maintain, adapt, and transmit the memory of current events and crime. These songs, shaped by a desire to preserve faithfully the details of local historical events and a need to adapt their storytelling to the poetic demands of the genre, give great insight into the customs and mentalities of the communities that performed them and passed them on through the generations, especially concerning questions of justice and morality. Studying these songs demonstrates from a methodological point of view the importance of comparing oral and written sources in order to better understand early modern society and culture.